Respuesta :
The center-radius form of the circle equation is in the format:
(x – h)2 + (y – k)2 = r2,
the center being at the point (h, k)
the radius being "r".
center: (5,3)
radius: 4
Using the equation: (x – h)2 + (y – k)2 = r2,
the circle equation is (x - 5)^2 + (y - 3)^2 = 4^2
the circle equation is (x - 5)^2 + (y - 3)^2 = 16
(x – h)2 + (y – k)2 = r2,
the center being at the point (h, k)
the radius being "r".
center: (5,3)
radius: 4
Using the equation: (x – h)2 + (y – k)2 = r2,
the circle equation is (x - 5)^2 + (y - 3)^2 = 4^2
the circle equation is (x - 5)^2 + (y - 3)^2 = 16